(3cJGH Jbhje GdfXQ aj eSGFd NdGajI PGFYI hfHP ePgHjI fGaYIs - (3GHf GdOgGf , aNQ GdOjf CHh TLGY eMeO Hf Ydj Hf TYjH Hf GdOgGf GdHZOGOj GdTGaYj,J (B592 (3g` s ((3fYje Hf eMeO GdbQTi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG ddgOi heG cfG dfgJOi dhdG Cf gOGfG Gddg Je LeYJ gPg GdChGQb hhSeJgG HJbhje GdfXQ JTJed Ydi eSGFd NdGajI PGFYI hfHP ePgHjI fGaYI s
(3BNQgG (B:s
(3jTGQc CMO MOjgG ddebOeI GdeSdeI hdGjSde ehLHJjf efgG cdjI Ch ehLHI hSGdHI efgeG cdjI hdGjJMQi Cf jSde LRFjJjf Ch SGdHJjf jJdhg LOhd GdJhGQjN s
(3HChdgG JedcGf CMOgeG eDQN SfI (B1115(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B15s
Keywords: (3CUhd Gdabgs